DECISION-MAKING MODELS, COHERENCE AND INTEGRITY IN THE CODE OF CIVIL PROCEDURE (Revista Paradigma, 2020)
The paper intends to answer if the decision-making model adopted by Brazilian courts (seriatim) is adequate to the political pretensions that resulted in the consecutive legislative reforms. Especially since Constitutional Amendment 45 of 2004, changes in procedural rules have been an attempt to give the judicial process celerity, isonomy and stability – the latter two expressed mainly in the duties imposed on the courts to maintain consistency and integrity in jurisprudence –, granting greater focus to the standardization of decisions in a movement that approximates the work of the Judiciary, in its typical function of jurisdictional provision, of the common law tradition. Among the main changes are the adoption of precedent as an element of argumentation and grounding of decisions, as well as the importation of the related figures, such as ratio decidendi, distinguishing and overruling. On this, based on the concepts of coherence and integrity developed by Ronald Dworkin in articulation with national authors who discourse from a coherent point of view, the objective is, from a comparative of the decision-making models per curiam and seriatim, to investigate whether current decision-making practice can or cannot comply with that was intended by legislative changes.